Incidence of and survival after subsequent cancers in carriers of pathogenic MMR variants with previous cancer: a report from the prospective Lynch syndrome database. Issue 9 (3rd June 2016) - Møller, Pål; Seppälä, Toni; Bernstein, Inge; Holinski-Feder, Elke; Sala, Paola; Evans, D Gareth; Lindblom, Annika; Macrae, Finlay; Blanco, Ignacio; Sijmons, Rolf; Jeffries, Jacqueline; Vasen, Hans; et al.
Abstract : Objective: Today most patients with Lynch syndrome (LS) survive their first cancer. There is limited information on the incidences and outcome of subsequent cancers. The present study addresses three questions: (i) what is the cumulative incidence of a subsequent cancer; (ii) in which organs do subsequent cancers occur; and (iii) what is the survival following these cancers? Design: Information was collated on prospectively organised surveillance and prospectively observed outcomes in patients with LS who had cancer prior to inclusion and analysed by age, gender and genetic variants. Results: 1273 patients with LS from 10 countries were followed up for 7753 observation years. 318 patients (25.7%) developed 341 first subsequent cancers, including colorectal (n=147, 43%), upper GI, pancreas or bile duct (n=37, 11%) and urinary tract (n=32, 10%). The cumulative incidences for any subsequent cancer from age 40 to age 70 years were 73% for pathogenic MLH1 ( path_MLH1 ), 76% for path_MSH2 carriers and 52% for path_MSH6 carriers, and for colorectal cancer (CRC) the cumulative incidences were 46%, 48% and 23%, respectively. Crude survival after any subsequent cancer was 82% (95% CI 76% to 87%) and 10-year crude survival after CRC was 91% (95% CI 83% to 95%). Conclusions: Relative incidence of subsequent cancer compared with incidence of first cancer was slightly but insignificantly higher than cancer incidence in patients with LS without previous cancer (range 0.94–1.49). The favourable survival after subsequent cancers validated continued follow-up to prevent death from cancer. The interactive website http://lscarisk.org was expanded to calculate the risks by gender, genetic variant and age for subsequent cancer for any patient with LS with previous cancer.